Pemberdayaan Kesehatan Perempuan Komunitas Batik Di Kecamatan Kerek, Kabupaten Tuban - sutinah sutinah; Hotman Siahaan; Musta'in Mashud (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2023)
This community service activity is motivated by the Covid-19 pandemic which has been going on since March 2020, because it is important for the community, especially women who work as batik craftsmen, to maintain their health. There are still many community members and women in the batik community who have not complied with the health protocol. This could be because you are not used to it, so you feel uncomfortable. For this reason, the Master of Sociology Study Program, Department of Sociology, FISIP Universitas Airlangga took the initiative to carry out community service activities to empower women in the batik community in the health sector in Kerek District, Tuban Regency, East Java. This service activity was attended by 50 women from the Bati community in Kerek District and took place in Gaji Village. To avoid crowds, the activity was carried out in two sessions and each session was attended by 25 people. Activities are carried out using mixed methods, namely online and offline. Participants attend and take part in activities in Gaji Village while the material is provided online. The material provided is knowledge about the coronavirus, prevention, and transmission of Covid-19, and the role of the family in dealing with family members when someone is sick. The results of the community service show that the knowledge of the service participants experienced a delay after the community service activities were carried out. This is shown from the results of the pre-test and post-test conducted during the activity.